2009
DOI: 10.1080/15555240902849008
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Trade Unions to the Community: Promoting Employment for Individuals with Mental Health Conditions

Abstract: The findings of a research effort that sought to define the mutual interests of unions and individuals with mental health conditions, their family members, and service providers are reported. The data were gathered from a nonrandom sample of trade union experts in disability policy and procedures. The research question posed is: What is the potential for unions to serve as a source of work options, valuable information on workplace cultures, and workplace supports to individuals with mental health conditions? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The synergistic relationship among these pillars and the constituency groups provides the framework for effective disability policy and positive employment outcomes for persons with disabilities. Akabas & Gates (2009) Individuals, and services provider, can benefit from support and advocacy by unions and, in turn, can offer unions respect and community support. This research effort identified the kind of bridges that exist and/or can be created between community, its mental health system and labor unions so that each may leverage the resources of the others to their own benefit at the same time that they serve the interest of individuals with mental health conditions and their families.…”
Section: Main Findingmentioning
confidence: 99%
See 4 more Smart Citations
“…The synergistic relationship among these pillars and the constituency groups provides the framework for effective disability policy and positive employment outcomes for persons with disabilities. Akabas & Gates (2009) Individuals, and services provider, can benefit from support and advocacy by unions and, in turn, can offer unions respect and community support. This research effort identified the kind of bridges that exist and/or can be created between community, its mental health system and labor unions so that each may leverage the resources of the others to their own benefit at the same time that they serve the interest of individuals with mental health conditions and their families.…”
Section: Main Findingmentioning
confidence: 99%
“…In addition to the policy and allegation, studies revealed that engaging employment specialists or rehabilitation personnel facilitated workplace integration, which underscores the importance of internal and external partnerships in integrating PWDs into the workplace (Akabas & Gates, 2009;Kulkarni et al, 2016;McFarlane, 1998;Wehman, 2003). Wehman (2003) stressed multiple factors for a successful workplace integration, as inclusion is fluid as work conditions change.…”
Section: Internal and External Partnershipmentioning
confidence: 99%
See 3 more Smart Citations